Optimasi formula sampo ekstrak daun pacar air (Impatiens balsamina L.) dengan kombinasi natrium lauril sulfat dan cocamide DEA - Dila Ayu Lestari; Yohanes Juliantoni; Raisya Hasina (Universitas Mataram, 2021)
Dandruff is an anomalous condition characterized by excessive exfoliation of the horny layer from the scalp. The leaves of the water henna plant (Impatiens balsamina L.) are one of the natural ingredients that have anti-dandruff properties, so they can be used as an active ingredient in making dandruff shampoo. The water henna leaves were extracted using the maceration method with ethanol 96%. Apart from the active ingredients, shampoo also has an important component, namely surfactants. The surfactant used in this study was a combination of sodium lauryl sulfate and cocamide DEA. The purpose of this study was to optimize the surfactant formula of sodium lauryl sulfate and cocamide DEA in water henna leaf extract shampoo. This research was a laboratory experimental research. Formula optimization was done through the Simplex Latice Design (SLD) method approach by making eight formulas. All formulas were evaluated for their physical properties including the foam height test and pH test. The data obtained were processed with Design Expert® software. Based on the physical evaluation of the water henna leaf extract shampoo, the results of the high foam test were 10,025 cm and a pH of 6,12. The results of the acceptability test of shampoo preparations including the parameters of color, smell, texture and viscosity received a fairly good response with the acquisition of values 3,1, 3,3, 3,9 and 4 with information 1 (very dislike), 2 (dislike), 3 (quite like), 4 (like) and 5 (really like). The optimum formula for the shampoo consisting of 5% water henna leaf extract, 1,1863% sodium lauryl sulfate, 19,814% cocamide DEA, 3% CMC, 0,5% citric acid, 0,5% methyl paraben, 0,15% menthol and distilled water had physical properties that meet the requirements of a good shampoo preparation.